Determination of caustic drain out period of glass bottle washer and impact of total and effective caustic strengths for glass bottle washing in soft drink plant - Marpana, R. A. U. J.; Harshani, B.M.MJ. (My University, 2016)
One of the most important processes in soft drink production is bottle washing; high quality of the product depends on that. A main objective of the present study is to determine the impact of total caustic and effective caustic strength on the washing performance of glass bottles. Total and effective caustic strength in samples were measured based on titration results. Four parameters were considered on the washing performance of glass bottles such as Microbiological Tests (APC and Yeast & Molds), Methylene blue test, Phenolphthalein test and Physical inspection. Ten samples were tested for every test per each time and three times were considered for a day and conduct for 43 days (within two caustic drains out periods). Negative correlations in between total, effective caustic strengths with time (Days) indicate from 29 days onward in tanks. There is a Positive correlation (P < 0.05) in between Carbonates (g/ml) and time (Days) onward. Positive correlations (P < 0.05) indicate from 35 days onward for the number of algae present bottles, number of dirty bottles and APC too. Twenty nine days from the initial charge of caustic soda can be taken as the most suitable day for the caustic discharge. Under the practical scenario, mean differences of total and effective caustic strengths (%) are negligible compared to the standard value and not significantly difference (P > 0.05).
Keywords: bottle washing; Total and effective caustic strength; Microbiological Tests; Methylene blue test; Phenolphthalein test; Physical inspection